Financial Communication in Small and Medium-Sized Enterprises Patents in Financial Communication - Zureck, Alexander; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2015)
To ensure refinancing opportunities for SMEs, answers for bridging the information gap between investor and company are needed; in this context, capital markets are becoming increasingly important. Alexander Zureck focuses on patents as an example of intangible assets and on their importance for the financial communication between SMEs and the capital market. A positive correlation between patent application and stock price development underscores the importance of patents. Based on his findings, the author recommends to take patents and other intangible assets into companys$1 (Bfinancial communication. Contents Financial Communication in the Context of Information Economics Financial Communication in Small and Medium-Sized Enterprises Patents in Financial Communication Target Groups Researchers, students, and practitioners in the field of economics with a focus on finance, communication and medium-sized enterprises The Author While Alexander Zureck studied business administration at FOM University of Applied Sciences, he worked in market research and in a bank. Today, he works for the FOM University of Applied Sciences in the field of financial research and he consults small and medium-sized enterprises.s
Financial Communication in the Context of Information Economics -- Financial Communication in Small and Medium-Sized Enterprises -- Patents in Financial Communication.
Keywords: Finance; Management; Industrial management; Macroeconomics; Finance; Finance, general; Innovation/Technology Management; Macroeconomics/Monetary Economics//Financial Economics; Electronic books